Aberrations of biochemical indicators in amyotrophic lateral sclerosis: a systematic review and meta-analysis - Cheng, Yangfan (Transl Neurodegener, 2021)
Accumulating evidence has suggested that the pathological changes in amyotrophic lateral sclerosis (ALS) are not only confined to the central nervous system but also occur in the peripheral circulating system. Here, we performed a meta-analysis based on the PubMed, EMBASE, EBSCO, and CNKI databases, to find out biochemical indicators associated with energy metabolism, iron homeostasis, and muscle injury that are altered in ALS patients and their correlations with ALS phenotypes. Forty-six studies covering 17 biochemical indicators, representing 5454 ALS patients and 7986 control subjects, were included in this meta-analysis. Four indicators, including fasting blood glucose level (weighted mean difference [WMD] = 0.13, 95% CI [0.06–0.21], p = 0.001), serum ferritin level (WMD = 63.42, 95% CI [48.12–78.73], p < 0.001), transferrin saturation coefficient level (WMD = 2.79, 95% CI [1.52–4.05], p < 0.001), and creatine kinase level (WMD = 80.29, 95% CI [32.90–127.67], p < 0.001), were significantly higher in the ALS patients, whereas the total iron-binding capacity (WMD = − 2.42, 95% CI [− 3.93, − 0.90], p = 0.002) was significantly lower in ALS patients than in the control subjects. In contrast, the other 12 candidates did not show significant differences between ALS patients and controls. Moreover, pooled hazard ratios (HR) showed significantly reduced survival (HR = 1.38, 95% CI [1.02–1.88], p = 0.039) of ALS patients with elevated serum ferritin levels. These findings suggest that abnormalities in energy metabolism and disruption of iron homeostasis are involved in the pathogenesis of ALS. In addition, the serum ferritin level is negatively associated with the overall survival of ALS patients. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s40035-020-00228-9.